2007
DOI: 10.1016/j.lfs.2007.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species trigger ischemic and pharmacological postconditioning: In vivo and in vitro characterization

Abstract: Reactive oxygen species (ROS) generated by ischemic and pharmacological preconditioning are known to act as triggers of cardiac protection; however, the involvement of ROS in ischemic and pharmacological postconditioning (PostC) in vivo and in vitro is unknown. We tested the hypothesis that ROS are involved in PostC in the mouse heart in vivo and in the isolated adult cardiac myocyte (ACM). Mice were subjected to 30 min coronary artery occlusion followed by 2 h of reperfusion with or without ischemic or pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 21 publications
6
113
0
2
Order By: Relevance
“…This supports the idea that the delayed recovery of intracellular pH during initial reperfusion, is mandatory to limit infarct size in PostC mainly via prevention of mPTP opening and prevention of RIRR [8,9,17,29,30,34,55]. Both in vitro and in vivo studies demonstrated that large spectrum ROSscavengers such as N-acetyl-L-cysteine (NAC) and/or N-(2-mercaptopropionyl)-glycine (MPG) given either during the PostC maneuvers [8,51,54,63] or during AB infusion [8,9,10,13] prevented their protective effects [13,51,54,63]. Moreover, addition of alkaline buffer in early reperfusion abolishes both AB-and PostC-protection [8,9,17,29,55].…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…This supports the idea that the delayed recovery of intracellular pH during initial reperfusion, is mandatory to limit infarct size in PostC mainly via prevention of mPTP opening and prevention of RIRR [8,9,17,29,30,34,55]. Both in vitro and in vivo studies demonstrated that large spectrum ROSscavengers such as N-acetyl-L-cysteine (NAC) and/or N-(2-mercaptopropionyl)-glycine (MPG) given either during the PostC maneuvers [8,51,54,63] or during AB infusion [8,9,10,13] prevented their protective effects [13,51,54,63]. Moreover, addition of alkaline buffer in early reperfusion abolishes both AB-and PostC-protection [8,9,17,29,55].…”
Section: Introductionsupporting
confidence: 63%
“…Moreover, we have studied these redox effects in the isolated hearts and could not predict whether the effects can be replicated in vivo. Nevertheless, we have shown a redox signaling in PostC in isolated heart [54] and this observation has been confirmed in vivo in different laboratories [8,9,63]. Also these new results need to be confirmed in vivo.…”
Section: Methodological Problemsmentioning
confidence: 51%
See 3 more Smart Citations